Acceptability and Feasibility of Maternal Mental Health Assessment When Managing Small, Nutritionally At-Risk Infants Aged < 6 Months: A Key Informant Interview Study - Natalie Mee; Mubarek Abera; Marko Kerac (MDPI AG, 2024)
Maternal mental health (MMH) conditions and infant malnutrition are both major global public health concerns. Despite a well-established link between the two, many nutrition programmes do not routinely consider MMH. New World Health Organization (WHO) malnutrition guidelines do, however, emphasise MMH. To inform guideline rollout, we aimed to assess the feasibility and acceptability of MMH assessments in nutrition programmes in low-resource settings. Ten semi-structured interviews were conducted with international key informants who work on nutrition programmes or MMH research. Interview transcripts were coded using subthemes derived from the key points discussed. The benefits and risks were highlighted. These included ethical dilemmas of asking about MMH if local treatment services are suboptimal. Commonly reported challenges included governance, staff training and finance. Community and programme staff perceptions of MMH were primarily negative across the different settings. Many points were raised for improvements and innovations in practice, but fundamental developments were related to governance, care pathways, advocacy, training, funding and using existing community networks. Future implementation research is needed to understand whether assessment is safe/beneficial (as it is in other settings) to promote MMH screening. Current service providers in low-resource settings can undertake several steps, as recommended in this paper, to improve the care offered to mothers and infants.